Sartre's Dialectical Methodology. Issue 48 (3rd April 2017) - Sherman, David
ABSTRACT: Sartre's intention in the Critique of Dialectical Reason is to establish the heuristic value of the dialectical method when applied to the social sciences. Toward this end, he furnishes an account of how, on the basis of natural needs, rational choices, burgeoning social ensembles, natural and social contingencies and unintended consequences, human beings make their history. I shall argue that his dialectical method, especially when modified, opens up interesting possibilities for clarifying the two most important and enduring meta-issues in the philosophy of social science: (1) whether social phenomena should be explained in terms of the beliefs, desires and actions of individuals or the rules and practices of social institutions ("Methodological Individualism" or "Methodological Holism") and (2) whether social phenomena should be explained in terms of causes, as in the natural sciences, or in terms of what they mean in their social contexts, as in hermeneutics and other interpretive approaches ("Explanation" or "Understanding").